Application of Rice Husk Biochar and Chicken Manure Bokashi on the Growth of Mustard Greens (Brasisca juncea L.) - Ilham, Dewi Jayagma; Meyuliana, Aulia; Elinda, Friza; Chrisnawati; Imtaz Sumbari, Ahmad (Universitas Medan Area, 2025)
Green mustard greens (Brassica juncea L.) are a type of horticultural plant that is widely cultivated in Indonesia. However, mustard greens production has continued to decline annually from 2020 to 2023. Efforts that can be made to optimize mustard greens production include increasing soil fertility by providing soil conditioners, such as rice husk biochar and chicken manure bokashi. This study aims to determine the provision of a combination of biochar and bokashi fertilizer that is good for increasing mustard greens' growth. This research was conducted in Sungai Janiah, Gunung Talang District, Solok Regency with an altitude of 490 meters above sea level from September to December 2024. The design used was Randomized Block Design (RAK) with treatments P0 = without organic fertilizer, P1 = 15 tons/ha Biochar (BC) P2 = 20 tons/ha Biochar (BC), P3 = 15 tons/ha Bokasi (Bok) P4 = 20 tons/ha Bokasi (Bok), P5 = 5 tons / ha biochar + 10 tons / ha Bokasi, P6 = 10 tons / ha biochar + 10 tons/ha Bokasi. The results of the research showed that the combination of 10 tons/ha biochar + 10 tons/ha Bokasi was significant on the parameters of plant height and consumption weight. Still, it was no significant on plant leaf width and number of leaves.